Mineral formation in the primary polyps of pocilloporoid corals. (15th September 2019) - Neder, Maayan; Laissue, Pierre Philippe; Akiva, Anat; Akkaynak, Derya; Albéric, Marie; Spaeker, Oliver; Politi, Yael; Pinkas, Iddo; Mass, Tali
Graphical abstract: Abstract: In reef-building corals, larval settlement and its rapid calcification provides a unique opportunity to study the bio-calcium carbonate formation mechanism involving skeleton morphological changes. Here we investigate the mineral formation of primary polyps, just after settlement, in two species of the pocilloporoid corals: Stylophora pistillata (Esper, 1797) and Pocillopora acuta (Lamarck, 1816). We show that the initial mineral phase is nascent Mg-Calcite, with rod-like morphology in P. acuta, and dumbbell morphology in S. pistillata . These structures constitute the first layer of the basal plate which is comparable to Rapid Accretion Deposits (Centers of Calcification, CoC) in adult coral skeleton. We found also that the rod-like/dumbbell Mg-Calcite structures in subsequent growth step will merge into larger aggregates by deposition of aragonite needles. Our results suggest that a biologically controlled mineralization of initial skeletal deposits occurs in three steps: first, vesicles filled with divalent ions are formed intracellularly. These vesicles are then transferred to the calcification site, forming nascent Mg-Calcite rod/pristine dumbbell structures. During the third step, aragonite crystals develop between these structures forming spherulite-like aggregates. Statement of Significance: Coral settlement and recruitment periods are highly sensitive to environmental conditions. Successful mineralization during these periods is vital and influences the coral's chances of survival. Therefore, understanding the exact mechanism underlying carbonate precipitation is highly important. Here, we used in vivo microscopy, spectroscopy and molecular methods to provide new insights into mineral development. We show that the primary polyp's mineral arsenal consists of two types of minerals: Mg-Calcite and aragonite. In addition, we provide new insights into the ion pathway by showing that divalent ions are concentrated in intracellular vesicles and are eventually deposited at the calcification site.